N-(2,6-Dimethylphenyl)-2,4-dimethylbenzenesulfonamide - Nirmala, P. G. (International Union of Crystallography, 2011)
Molecules of the title compound, C(16)H(19)NO(2)S, are bent at the S atom with a C—SO(2)—NH—C torsion angle of −60.0 (2)°. The dihedral angle between the phenylsulfonyl and aniline rings is 41.7 (1)°. In the crystal, molecules are packed into centrosymmetric dimers through pairs of N—H⋯O(S) hydrogen bonds.